1996
DOI: 10.1089/thy.1996.6.319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iodide on Thyroglobulin Biosynthesis in FRTL-5 Cells

Abstract: Iodide inhibits several thyroid parameters through an organic intermediate, and this process has been related to thyroid autoregulation. The aim of this study was to determine the effect of iodine on thyroglobulin (Tg) synthesis in the rat thyroid cell line FRTL-5. TSH stimulated amino acid incorporation into the cells by 400% and iodine had no effect on this parameter. No effect of TSH or iodide on [35S] methionine incorporation into protein was found under our experimental conditions (approximately 80% of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…4B). The result is in agreement with the study of Pregliasco et al done in FRTL-5 (21). In addition, we showed that 25 U=mL of IFN-g with different doses of KI (1 or 100 mM) did not change the Tg level, while a combination of KI with low-dose IFN-g (2 U= mL) normalized Tg secretion, compared with IFN-g alone ( p < 0.05, Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4B). The result is in agreement with the study of Pregliasco et al done in FRTL-5 (21). In addition, we showed that 25 U=mL of IFN-g with different doses of KI (1 or 100 mM) did not change the Tg level, while a combination of KI with low-dose IFN-g (2 U= mL) normalized Tg secretion, compared with IFN-g alone ( p < 0.05, Fig.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that ICAM-1 mRNA was doubled in suspension of isolated human thyroid follicles incubated with 10 mM sodium iodide (NaI) (20). Furthermore, iodide excess did not change Tg level in FRTL-5 cells (21), but it did inhibit iodine organification (22), thyroid hormone secretion (23), and cAMP formation (24) in isolated human thyroid follicles.…”
Section: Introductionmentioning
confidence: 99%
“…Its expression was found to be modulated by high and physiological concentrations of iodide in vitro (Morand et al, 2003;Leoni et al, 2008;Serrano-Nascimento et al, 2016) and in vivo studies (Uyttersprot et al, 1997;Eng et al, 1999;Maier et al, 2007). Regarding Tg, other gene downregulated by 2-IHDA, exposure to a high dose of iodide reduces its expression in PCCl3 cells (Leoni et al, 2008;Serrano-Nascimento et al, 2016) and in bovine follicles (Thomasz et al, 2010b) while no effect was found by others (Pregliasco et al, 1996;Uyttersprot et al, 1997;Suzuki et al, 1998;Eng et al, 1999;Kostic et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…It has also been reported that ICAM-1 mRNA was doubled in suspensions of isolated human thyroid follicles incubated with 10 mM sodium iodide (NaI) (Yamazaki et al, 2003). Furthermore, iodide excess did not change Tg level in FRTL-5 cells (Pregliasco et al, 1996), but it inhibited iodine organification (Davies et al, 1989), thyroid hormone secretion (Sato et al, 1990), and cAMP production and secretion (Miyazaki et al, 1999) in isolated human thyroid follicles. Recently, it was reported (Kostic et al, 2009) that iodide excess inhibited human primary thyroid cell proliferation and gradually increased ICAM-1 on cell surface.…”
Section: The Possible Role Of Iodide Excess On Thyroid Mild Inflammatmentioning
confidence: 94%